2018
DOI: 10.3390/biology7030043
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plastidial and Nuclear SSR Markers for Understanding Invasion Histories and Genetic Diversity of Schinus molle L.

Abstract: Invasive plant species are expected to display high dispersal capacity but low levels of genetic diversity due to the founder effect occurring at each invasion episode. Understanding the history of invasions and the levels of genetic diversity of such species is an important task for planning management and monitoring strategy for these events. Peruvian Peppertree (Schinus molle L.) is a pioneer tree species native from South America which was introduced in North America, Europe and Africa, becoming a threat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…SSR loci are repetitive elements found in nuclear and organellar genomes and are widely employed in genetic studies (Lemos et al 2018). The plastid SSR loci identified in this study have potential usefulness as molecular markers for studies of species and even cultivars differentiation.…”
Section: Discussionmentioning
confidence: 84%
“…SSR loci are repetitive elements found in nuclear and organellar genomes and are widely employed in genetic studies (Lemos et al 2018). The plastid SSR loci identified in this study have potential usefulness as molecular markers for studies of species and even cultivars differentiation.…”
Section: Discussionmentioning
confidence: 84%
“…Nogueira et al (2016) evaluated the transferability of 158 SSR from Psidium guajava L. in 18 fruit trees of the genera Eugenia and obtained promising results, but further studies are needed to validate these markers in larger populations. Sarzi et al (2019) using the methodology described by Lemos et al (2018) used the new generation sequencing technology to identify microsatellite in loci, which were prospected using partial sequencing of the E. uniflora genome. The authors developed 69 SSR markers, of which, after in silico evaluation, 30 primers prospected, however, when tested in the laboratory, they were partially successful, with only 12 markers showing amplification and with reduced band quality (Beise 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Simple repeats, the most frequent repetitive element in this WGSAS, represent, in turn, recombination ''hotspots'' of genome reorganization (Mehrotra and Goyal 2014). Given the high frequency and usual hypervariability of tandem simple sequence repeats (SSRs) in plant genomes, high-throughput sequencing has been largely used as a tool for the characterization of SSR genetic markers of non-model species (e.g., Staton et al 2015;Lemos et al 2018). In a former study, a total of 111 diand tri-nucleotides SSR regions were identified in E. uniflora using the same WGSAS of this study (Sarzi et al 2019).…”
Section: Discussionmentioning
confidence: 99%